Fatigue life prediction of pedicle screw for spinal surgery (Fracture and Structural Integrity, 2015)
This paper is dedicated to fatigue estimation of implants for spinal surgery. This article deals especially with special case of hollow pedicle screw. Implant systems utilizing specially designed spinal instrumentation are often used in these surgical procedures. The most common surgical procedure is spinal fusion, also known as spondylodesis, is a surgical technique used to join two or more vertebra. Implants are subjected to many loading cycles during their life, especially in the case of other degenerative changes in the skeleton, there are often changes in loading conditions, which often cannot be accurately determined. These changes often lead to further bending load in the thread. Hollow screws studied in this work show higher fatigue resistance than other types of implants.
Keywords: Pedicle-screw; Titan alloy; Fatigue life; Finite element analysis